Large eddy simulation of reacting flow in a hydrogen jet into supersonic cross-flow combustor with an inlet compression ramp. (29th June 2017) - Zhao, Majie; Zhou, Taotao; Ye, Taohong; Zhu, Minming; Zhang, Hongda
Abstract: Large eddy simulation (LES) has been performed to investigate transverse hydrogen jet mixing and combustion process in a scramjet combustor model with a compression ramp at inlet to generate shock train. Partially Stirred Reactor (PaSR) sub-grid combustion model with a skeleton of 19 reactions and 9 species hydrogen/air reaction mechanism was used. The numerical solver is implemented in an Open Source Field Operation and Manipulation (OpenFOAM) and validated against experimental data in terms of mean wall pressure. Effects of a shock train induced by the inlet compression ramp on the flame stabilization process are then studied. It can be observed that the interaction of the oblique shock and the jet mixing layer enhance the combustion and stabilize the flame. Symmetrical recirculation zone, which contributes to the flame anchoring of the supersonic transverse jet combustion, is observed in the near wall region of 10 < x/D < 20. The hydrogen fuel is transported from the center of jet plume to the near wall region on both sides of the central plane (z/D = 0) and thus intense combustion near the wall is observed due to the enhanced mixing and shock compression heating. Besides, the jet penetration in the reacting field is different from that in non-reacting case with the influence of the interaction between the reflected oblique shock and the jet shear layer on the windward side. Highlights: Effects of the shock train induced by an inlet compression ramp on the flame stabilization are studied. The supersonic flame structures are identified. The jet penetration in the reacting and non-reacting field are compared.